Kinetic scrape off layer simulations with semi-Lagrangian discontinuous Galerkin schemes - Einkemmer, Lukas; Moriggl, Alexander (Computer physics communications, 2025)
In this paper we propose a semi-Lagrangian discontinuous Galerkin solver for the simulation of the scrape off layer for an electron-ion plasma. We use a time adaptive velocity space to deal with fast particles leaving the computational domain, a block structured mesh to resolve the sharp gradient in the plasma sheath, and limiters to avoid oscillations in the density function. In particular, we propose a limiter that can be computed directly from the information used in the semi-Lagrangian discontinuous Galerkin advection step. This limiter can be directly implemented as part of the GPU kernel of the scheme, which avoids an expensive post processing step. We provide numerical results for a set of benchmark problems and compare different limiting strategies.